1994
DOI: 10.1111/j.1095-8649.1994.tb01225.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative ventricular weight of wild Atlantic salmon parr in relation to sex, gonad maturation and migratory activity

Abstract: Relative ventricular weight (RVW, ventricular weight/body weight · 100) was measured for five groups of Atlantic salmon parr from the Girnock Burn in Scotland. The mean RVW was: mature males, 0.087; immature resident males, 0.054; immature resident females, 0.056; immature migrant males, 0.056; immature migrant females, 0.053. For a group of mature male parr from the R. Nith, Galloway, Scotland, the mean RVW was 0.108. There were no significant differences in the RVW between groups of immature fish. The RVW of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Although cardiac hypertrophy in males also has been demonstrated during sexual maturation in other fish species (4,42), this study on sockeye suggests that the profound cardiac hypertrophy observed in male rainbow trout during sexual maturation is not a general trait among all salmonid species. It is possible that differences in life history between sockeye and rainbow trout may explain these discrepancies.…”
Section: Discussionmentioning
confidence: 90%
“…Although cardiac hypertrophy in males also has been demonstrated during sexual maturation in other fish species (4,42), this study on sockeye suggests that the profound cardiac hypertrophy observed in male rainbow trout during sexual maturation is not a general trait among all salmonid species. It is possible that differences in life history between sockeye and rainbow trout may explain these discrepancies.…”
Section: Discussionmentioning
confidence: 90%
“…Arndt (2000) recorded low growth of males relative to immature fish in the final stages of gonad maturation (September), suggesting that there is a switch from high to low growth as maturation proceeds. This latter low growth phase may relate to increased maintenance costs associated with the increase in the mass of highly metabolically active tissues, such as heart ventricle, that occurs prior to spawning (Armstrong & West 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dimorphism in heart weight in salmonids has been examined previously, with studies often reporting larger heart sizes in males or no sexual dimorphism at all; however, of these studies, few have done so in a statistically robust manner. For example, studies have either not taken into account variation in body size [66], or body size is considered through simple divisional indexes such as RHM [60,[67][68][69]. The use of ratios and divisional indexes has been widely criticized in the literature, as they are inadequate for removing size correlations from morphological data [70,71].…”
Section: Sexual Dimorphismmentioning
confidence: 99%